Immunohistochemical and Clinicopathologic Profiling of Pituitary Adenomas at a Nigerian Tertiary Hospital - Uchime KE; Ajayi OO; Awolola NA; Bankole OB; Anunobi CC (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2024)
Background: Pituitary adenoma is the most common pituitary tumour and the third most common intracranial tumour worldwide. Only a few studies have been done in Africa on the immunohistochemical expression pattern and clinicopathologic presentations of the different hormonal subtypes of pituitary adenomas. Objective: To evaluate the immunohistochemical hormonal profiles and clinicopathologic behaviour of pituitary adenomas diagnosed within ten years at the Lagos University Teaching Hospital, Lagos, Nigeria. Methods: In this 10-year retrospective, cross-sectional study, all cases of pituitary adenomas diagnosed at the hospital mentioned above between 1 January 2009 and 31 December 2018 were analysed. Their paraffin-embedded tissue blocks were stained with haematoxylin and eosin and then with immunostains for growth hormome (GH), adrenocorticotrophic hormone (ACTH), thyroid stimulating hormone (TSH), follicular stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL), using their standard immunohistochemistry protocols. Results: Seventy pituitary adenoma cases were studied. The male-to-female ratio of the patients was 1.6:1. The median age was 45 years, and the peak age of occurrence was the fifth decade for both sexes. Most were null cell adenomas (44.7%) and FSH-beta gonadotrophs (22.9%). The least diagnosed were thyrotroph (1.4%) and corticotroph adenomas (1.4%). Most of the adenomas were macroadenomas, and the most common presenting symptom was visual impairment. Conclusion: Pituitary adenoma is commoner in males in their 5th decade of life at the Lagos University Teaching Hospital, Lagos, Nigeria. The null cell adenoma is the commonest type of pituitary adenoma diagnosed in the center, and the majority of the patient diagnosed with pituitary adenoma present late with complications of visual impairment.